2012
DOI: 10.1007/s11695-012-0669-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor-1 Concentrations Are Reduced in Severely Obese Women and Raise After Weight Loss Induced by Laparoscopic Adjustable Gastric Banding

Abstract: (1) Severely obese women have low IGF-1 serum levels with respect to normal weight age-matched controls; (2) the extent of IGF-1 deficiency is proportional to increased BMI; (3) after LAGB a spontaneous raise of serum IGF-1 occurs, proportional to the extent of weight reduction; and (4) serum IGF-1 in severely obese subjects may have a limited value for detection of hypothalamic-pituitary diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
1
28
0
2
Order By: Relevance
“…1). This blunted effect of loading in the old participants on leg lean mass may possibly be attributed to lower levels of anabolic circulating hormones such as insulin-like growth factor-1 (IGF-I) (Galli et al 2012) and the increase of catabolic cytokines such as interleukin-6 (IL-6) and tumour necrosis factor α (TNF-α) (Visser et al 2002; Hotamisligil et al 1995) seen in older vs. younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…1). This blunted effect of loading in the old participants on leg lean mass may possibly be attributed to lower levels of anabolic circulating hormones such as insulin-like growth factor-1 (IGF-I) (Galli et al 2012) and the increase of catabolic cytokines such as interleukin-6 (IL-6) and tumour necrosis factor α (TNF-α) (Visser et al 2002; Hotamisligil et al 1995) seen in older vs. younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It may be hypothesized that a too rapid and intense loss of weight, obtained by some bariatric surgical procedures, mostly those with a malabsorptive component, may favor a persistent pathologically low IGF1. Galli et al (23) showed a good correlation between a WL of about 23% and IGF1 increase, after 2 years of follow-up with banding. On the other hand, other investigators, i.e.…”
Section: Discussionmentioning
confidence: 91%
“…The somatotropic axis is also affected by severe obesity, and reduced basal and stimulated GH secretion and IGF1 concentrations have been described in obese subjects (15,16,17,18,22,23). The somatotropic axis is relevant for healthy condition at all ages and it is understood that low IGF1 concentrations have been closely associated with cardiovascular disease (11), abnormal abdominal adiposity accumulation, low quality of life, decreased muscle mass, and abnormal bone homeostasis (11,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations